Humanitarian aid and christian mission in the globalized world: Impulses of Lausanne Movement - Fertig, Maerly Cristine Schaeffer (Vox Scripturae - Revista Teológica Internacional, 2015)
This qualitative study addresses the themes of Globalization, Humanitarian Aid and Christian Mission, primarily with conceptual visions from the Theology and International Relations that link to new global players serving to alleviate human suffering, material and spiritual. The emphasis then lies in the approach of the Lausanne Movement and the Letter to the Ephesians, discussing the challenges of Christian Mission to the aid of humanity.
Keywords: Dilemmas of Globalization; Humanitarian Aid; Christian Mission